Nucleotide excision repair gene polymorphisms may predict acute toxicity in patients treated with chemoradiotherapy for bladder cancer. (October 2010) - Sakano, Shigeru; Hinoda, Yuji; Sasaki, Miwa; Wada, Takashi; Matsumoto, Hiroaki; Eguchi, Satoshi; Shinohara, Asano; Kawai, Yoshihisa; Hara, Tomohiko; Nagao, Kazuhiro; Hara, Takahiko; Naito, Katsusuke; et al.
Aims: Platinum-based chemoradiotherapy (CRT) as bladder conservation therapy has shown promising results for muscle-invasive bladder cancer. However, treatment-related toxicity remains a major consideration in therapeutic planning. Some common polymorphisms in genes involved in DNA repair (encoding enzymes that repair DNA damaged by platinum agents and ionizing radiation) are reported to result in modulation of the repair capacity. We investigated associations between functional genetic polymorphisms involved in DNA repair and acute toxicity of CRT to determine the predictive value of these polymorphisms for toxicity.Materials & methods: The study group comprised of 101 bladder cancer patients treated with platinum-based CRT, and seven polymorphisms in XPC (Lys939Gln, rs2228001), XPD (Lys751Gln, rs13181), XPG (Asp1104His, rs17655), XRCC1 (Arg399Gln, rs25487), XRCC3 (Thr241Met, rs861539), TP53 (Arg72Pro, rs1042522) and MDM2 (SNP309, T>G, rs2279744) were genotyped.Results: More than two total variant alleles in nucleotide excision repair genes, including XPC, XPD and XPG, were significantly associated with grade 3 or 4 neutropenia (adjusted odds ratio [aOR]: 6.8; 95% CI: 2.0–26; p = 0.0026). There were no significant associations between any genotypes and grade 2 or greater nausea/vomiting or diarrhea. Any grade 3 or 4 hematological toxicity was significantly associated with the Gln/Gln or Lys/Gln + Gln/Gln genotypes of XPC compared with Lys/Lys (aOR: 10; 95% CI: 2.0–65; p = 0.0070 or aOR: 6.3; 95% CI: 1.9–29; p = 0.0069; respectively).Conclusion: These results suggest that nucleotide excision repair gene polymorphisms, especially in XPC, might potentially be predictive factors for acute toxicity of CRT for bladder cancer, helping individual patient selection for bladder conservation therapy. However, further studies with larger sample sizes are needed to draw final conclusions.